Application of metal nickel modified red mud-based catalyst in catalytic pyrolysis of wood-plastic composite material
By using nickel for modified red mud, metal nickel modified red mud is prepared and applied to the catalytic pyrolysis of wood-plastic composite materials, the problems of low waste utilization efficiency and insufficient catalytic activity of red mud in the prior art are solved, and efficient resource utilization and catalytic activity are achieved.
Patent Information
- Application Number
- CN202510025823.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively utilize wood-plastic composite waste, and the catalytic activity of red mud is insufficient, which limits its application in industrial production.
By using the transition metal nickel (Ni) for modified red mud, a metal nickel modified red mud is prepared and applied to the catalytic pyrolysis process of wood-plastic composites.
It realizes efficient resource utilization of wood-plastic composite waste, prepares gas-phase products rich in hydrogen and liquid-phase products rich in aromatic hydrocarbons, and enhances the catalytic activity and industrial application value of red mud.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste resource utilization, and specifically relates to the application of a metal nickel-modified red mud-based catalyst in catalytic pyrolysis of wood-plastic composite materials. Background Art
[0002] Wood-plastic composite materials are a new type of composite material formed by melting and mixing biomass fibers and thermoplastics in a certain proportion (extrusion, mixing, injection molding, hot pressing and other processes), which has the advantages of both wood and plastic. Wood-plastic composite materials have good processing characteristics, mechanical properties, water resistance, corrosion resistance, long service life and other advantages. Its products are widely used in municipal administration, gardening, building materials, furniture, logistics packaging and other industries. Although wood-plastic composite materials can be repeatedly processed and recycled, the macromolecules will gradually degrade and deteriorate the material performance, and a large amount of new waste will be generated, which also faces the problem of harmless treatment.
[0003] Wood-plastic composite materials are composite materials with plastic as the matrix and biomass fibers as the reinforcement. The biomass of the two main components is a renewable carbon source, and waste plastics are petroleum derivatives. Both are material energy sources and can be used to prepare high-value-added chemicals through catalytic pyrolysis technology, thereby effectively realizing the resource utilization of waste, improving the utilization efficiency of wood-plastic composite materials resources, and meeting the requirements of compound circular economy and low-carbon economy.
[0004] Red mud (RM), also known as bauxite slag, is a waste produced during the production of the aluminum industry. It is composed of catalytically active metal oxides. In 2023, my country's red mud production was 107 million tons, the global production was about 180 million tons, and the utilization was about 13 million tons, with a comprehensive utilization rate of only 7.2%. In 2024, my country's red mud utilization is expected to exceed 13 million tons. Red mud is used as a catalyst, with the advantages of low price, rich chemical composition (Fe2O3, Na2O, SiO2, TiO2), and abundant reserves. Red mud has been used in a variety of different catalytic reactions, such as biomass pyrolysis, hydrogenation and liquefaction. During the co-pyrolysis process, red mud promotes the synergistic effect between hydrogen-rich plastics and solid biomass, eliminates oxygen and produces hydrocarbon-rich oil. In order to further improve the activity of red mud, increase the value of chemicals, and reduce the amount of catalyst used, red mud needs to be modified by metal loading.
[0005] Chinese patent CN 104511278 A discloses a method for preparing a red mud-loaded nickel catalyst, the purpose of which is to effectively solve the two major problems of red mud waste resource utilization and industrial production of cheap ammonia decomposition hydrogen production catalyst.
[0006] CN 111068727 A discloses a method for preparing aromatic hydrocarbons by pyrolysis of wood-plastic composite waste catalyzed by activated carbon. Specifically, the wood-plastic composite waste is used as raw material and activated carbon is used as catalyst, which are respectively placed in a fixed bed reactor, and then rapidly catalytically pyrolyzed in a nitrogen atmosphere. After condensing the catalytic pyrolysis gas, a liquid product rich in aromatic hydrocarbon compounds can be obtained.
[0007] The invention adopts transition metal nickel Ni to modify red mud to obtain a metal nickel-modified red mud-based catalyst, and uses the prepared composite catalyst for catalytic pyrolysis of actual wood-plastic composite materials, thereby promoting the value upgrade of pyrolysis products of actual wood-plastic composite materials. Summary of the invention
[0008] The purpose of the present invention is to provide an application of a metal nickel modified red mud-based catalyst in catalytic pyrolysis of wood-plastic composite materials. The present invention uses a freshly prepared metal nickel modified red mud-based catalyst to catalytically pyrolyze wood-plastic composite waste, specifically, the metal nickel modified red mud-based catalyst and the wood-plastic composite waste are placed in a vertical tubular furnace, and catalytic pyrolysis is performed under an inert gas atmosphere, so that a hydrogen-rich gas phase product and an aromatics-rich liquid phase product can be obtained.
[0009] The present invention provides an application of a metal nickel-modified red mud-based catalyst in catalytic pyrolysis of a wood-plastic composite material, which specifically comprises the following steps: 1) The raw red mud is washed with deionized water, and the washed red mud is placed in a muffle furnace and calcined for 2 to 4 hours at a calcination temperature of 500 to 700°C and a heating rate of 5 to 10°C / min. The red mud is then ground and passed through a 60 to 90 mesh sieve; 2) dissolving the soluble nickel salt in deionized water, adding the red mud powder obtained above, stirring thoroughly at 50-70° C. for 5-10 hours, and drying the obtained mixed solution in a forced air drying oven at 100-120° C. to a solid product of constant weight; 3) After the solid product is cooled, it is placed in a tubular furnace, heated to 400-700°C at a heating rate of 10°C / min and reduced at a constant temperature for 5 hours to obtain a metal nickel-modified red mud-based catalyst.
[0010] The soluble nickel salt is nickel chloride, nickel nitrate, nickel sulfate and nickel acetate, preferably nickel nitrate.
[0011] The loading amount of transition metal nickel in the red mud-based catalyst is 5% to 20%.
[0012] 4) placing the red mud-based catalyst and the wood-plastic composite material into a vertical tube furnace, and performing catalytic pyrolysis in a nitrogen atmosphere at a pyrolysis temperature of 500-700° C. to obtain a hydrogen-rich gas phase product and an aromatics-rich liquid phase product; The nitrogen flow rate is 30 ml / min and the pyrolysis is carried out for 10 to 30 minutes.
[0013] The ratio of the red mud-based catalyst to the substrate in the catalytic pyrolysis process is 0% to 40%.
[0014] The wood (material) plastic composite material comprises wood and plastic; the wood is wood fiber or crop straw, such as pine, but not limited to pine; the plastic is low-density polyethylene (LDPE), polyethylene (PE), polyvinyl chloride or polypropylene, but not limited to low-density polyethylene, polyvinyl chloride or polypropylene. Optionally, the mass ratio of low-density polyethylene or polyvinyl chloride to pine is 1:4.
[0015] The present invention provides an application of a metal nickel-modified red mud-based catalyst in catalytic pyrolysis of wood-plastic composite materials. The beneficial effects are as follows: the present invention uses a red mud-based catalyst to catalytically pyrolyze simulated wood-plastic composite materials and actual wood-plastic composite material wastes to prepare hydrogen-rich gas phase products and aromatic hydrocarbon-rich liquid phase products. The red mud-based catalyst used in the present invention is obtained by loading transition metal nickel on industrial waste red mud through an impregnation method to prepare a composite catalyst. Red mud is a waste generated in the production process of the aluminum industry, and has the advantages of low price, abundant reserves, and green environmental protection. Moreover, the red mud is composed of catalytically active metal oxides, which can promote the synergistic effect between hydrogen-rich plastics and solid biomass in actual wood-plastic composite materials, eliminate oxygen and produce hydrocarbon-rich oil.
[0016] The invention proposes a method for efficient resource utilization of actual wood-plastic composite material waste, which can effectively solve the resource utilization of red mud waste, industrial production of cheap hydrogen and aromatic-rich compounds, and can produce good environmental and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope image of the catalyst obtained in Example 1.
[0018] Figure 2 This is a scanning electron microscope image of the catalyst obtained in Example 2.
[0019] Figure 3 This is a gas-liquid-solid three-phase yield diagram obtained in Examples 3-5.
[0020] Figure 4 This is the gas-liquid-solid three-phase yield diagram obtained in Example 6-7.
[0021] Figure 5 This is a gas-liquid-solid three-phase yield diagram obtained in Examples 8-9.
[0022] Figure 6 This is the distribution diagram of the liquid phase product obtained in Examples 8-9. DETAILED DESCRIPTION
[0023] The present invention provides a method for catalytically pyrolyzing wood-plastic composite waste using a red mud-based catalyst. The present invention will be further described below in conjunction with specific embodiments.
[0024] The experimental methods and tests without specific conditions specified in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer; the general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified. Example
[0025] 10g of original red mud was washed with deionized water for more than 3 times, put into a muffle furnace, calcined at 600℃ for 4h, ground, passed through a 90-mesh sieve, weighed 0.526g of nickel nitrate hexahydrate and dissolved in 100ml of deionized water, added 10g of red mud and stirred at 70℃ for 5h, then the mixed solution was dried to constant weight at 120℃ in a blast drying oven, put into a muffle furnace, calcined at 600℃ for 4h to obtain a catalyst precursor, cooled and put into a tubular furnace, heated to 450℃ at a heating rate of 10℃ / min and reduced at a constant temperature for 5h to obtain a metal nickel-modified red mud-based catalyst 5%Ni-RM. Scanning electron microscope image is shown in Figure 1 . Example
[0026] 10g of the original red mud was washed with deionized water for 3 times, placed in a muffle furnace, calcined at 600°C for 4h, ground, passed through a 90-mesh sieve, 2.5g of nickel nitrate hexahydrate was weighed and dissolved in 100ml of deionized water, 10g of red mud was added and stirred at 70°C for 5h, and then the mixed solution was dried to constant weight at 120°C in a blast drying oven, and then placed in a muffle furnace and calcined at 600°C for 4h to obtain a catalyst precursor. After cooling, it was placed in a tubular furnace, heated to 450°C at a heating rate of 10°C / min and reduced at a constant temperature for 5h to obtain a metal nickel-modified red mud-based catalyst 20% Ni-RM. Scanning electron microscope image is shown in Figure 2 . Example
[0027] Take 4g simulated wood-plastic composite material (passed through 60 mesh sieve) as raw material, where the mass ratio of low-density polyethylene (passed through 60 mesh sieve) to pine wood in the wood-plastic mixed substrate is 1:4, put them into a vertical tube furnace, and pyrolyze them for 30min at 550℃, heating rate 10℃ / min, and nitrogen flow rate 30ml / min. Collect the gas-liquid-solid three-phase products and calculate the product yield. The specific results are shown in Figure 3 ; The gas phase product was detected and analyzed by gas chromatography, and the specific results are shown in Table 1; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 1. Example
[0028] 1.6g of the red mud-based catalyst prepared in Example 1 was used as a catalyst, and 4g of a simulated wood-plastic composite material (passed through a 60-mesh sieve) was used as a raw material, wherein the mass ratio of low-density polyethylene to pine wood in the wood-plastic mixed substrate was 1:4. The two were placed in a vertical tube furnace and pyrolyzed for 30min at 550°C, a heating rate of 10°C / min, and a nitrogen flow rate of 30ml / min. The gas-liquid-solid three-phase products were collected and the product yield was calculated. The specific results are shown in Figure 3 ; The gas phase product was detected and analyzed by gas chromatography, and the specific results are shown in Table 1; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 1. Example
[0029] 1.6g of the red mud-based catalyst prepared in Example 2 was used as a catalyst, and 4g of a simulated wood-plastic composite material (passed through a 60-mesh sieve) was used as a raw material, wherein the mass ratio of low-density polyethylene to pine wood in the wood-plastic mixed substrate was 1:4. The two were placed in a vertical tube furnace and pyrolyzed for 30min at 500°C, a heating rate of 10°C / min, and a nitrogen flow rate of 30ml / min. The gas-liquid-solid three-phase products were collected and the product yield was calculated. The specific results are shown in Figure 3 ; The gas phase product was detected and analyzed by gas chromatography, and the specific results are shown in Table 1; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 1.
[0030]
[0031] As can be seen from Table 1, when the simulated wood-plastic composite material is used as the substrate, the hydrogen content in the gas phase product increases significantly after the catalyst is added, from 32.49ml to 170.00ml and 163.38ml respectively. The aromatic content in the liquid phase product also increases; at the same time, the red mud-based catalyst with different nickel loadings has different effects on the distribution regulation of pyrolysis products. The 5% nickel loading has a more obvious effect on the product distribution regulation of the gas phase product, while the 20% nickel loading has a more obvious effect on the product distribution regulation of the liquid phase product. Example
[0032] 1.6g of the red mud-based catalyst prepared in Example 1 was used as a catalyst, and 4g of a simulated wood-plastic composite material (passed through a 60-mesh sieve) was used as a raw material, wherein the mass ratio of low-density polyethylene to pine wood in the wood-plastic mixed substrate was 1:4. The two were placed in a vertical tube furnace and pyrolyzed for 30min at 500°C, a heating rate of 10°C / min, and a nitrogen flow rate of 30ml / min. The gas-liquid-solid three-phase products were collected and the product yield was calculated. The specific results are shown in Figure 4; The gas phase product was detected and analyzed by gas chromatograph, and the specific results are shown in Table 2; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 2. Example
[0033] 1.6g of the red mud-based catalyst prepared in Example 1 was used as a catalyst, and 4g of a simulated wood-plastic composite material (passed through a 60-mesh sieve) was used as a raw material, wherein the mass ratio of low-density polyethylene to pine wood in the wood-plastic mixed substrate was 1:4. The two were placed in a vertical tube furnace and pyrolyzed for 30min at 700℃, a heating rate of 10℃ / min, and a nitrogen flow rate of 30ml / min. The gas-liquid-solid three-phase products were collected and the product yield was calculated. The specific results are shown in Figure 4 ; The gas phase product was detected and analyzed by gas chromatograph, and the specific results are shown in Table 2; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 2.
[0034]
[0035] It can be seen from Table 2 that when the simulated wood-plastic composite material is used as the substrate, increasing the pyrolysis temperature is more conducive to the production of valuable chemicals, and as the temperature increases from 500°C to 700°C, the aromatic content in the liquid product gradually increases, while the hydrogen content in the gas product first increases and then decreases slightly, reaching a maximum of 170.99 ml at 550°C. Example
[0036] Take 4g of actual wood-plastic composite material (passed through a 60-mesh sieve) as raw material, where the wood-plastic composite material is composed of polyethylene and pine wood powder, put it into a vertical tube furnace, and pyrolyze it for 30min at 550℃, a heating rate of 10℃ / min, and a nitrogen flow rate of 30ml / min. Collect the gas-liquid-solid three-phase products and calculate the product yield. The specific results are shown in Figure 5 ; The gas phase product was detected and analyzed by gas chromatography, and the specific results are shown in Table 3; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 3, and the specific liquid phase product distribution is shown in Figure 6 . Example
[0037] 1.6 g of the red mud-based catalyst prepared in Example 1 was used as a catalyst, and 4 g of an actual wood-plastic composite material (passed through a 60-mesh sieve) was used as a raw material, wherein the wood-plastic composite material was composed of polyethylene and pine wood powder. The two were placed in a vertical tube furnace and pyrolyzed for 30 min at 550 ° C, a heating rate of 10 ° C / min, and a nitrogen flow rate of 30 ml / min. The gas-liquid-solid three-phase products were collected and the product yield was calculated. The specific results are shown in Figure 5; The gas phase product was detected and analyzed by gas chromatography, and the specific results are shown in Table 3; the liquid phase product was detected and analyzed by gas chromatography-mass spectrometry, and the specific results are shown in Table 3. The specific distribution of liquid phase products is shown in Figure 6 .
[0038]
[0039] It can be seen from Table 3 that when the actual wood-plastic composite material is used as the substrate, after adding the red mud-based catalyst, the hydrogen production in the gas phase product increases significantly from 18.48ml to 113.02ml, and the content of aromatics in the liquid phase product also increases from 2.11% to 4.34%.
[0040] Depend on Figure 1-2 It can be seen that the surface of the metal nickel-modified red mud-based catalyst is relatively rough, mainly existing in the form of particle aggregates, with a large specific surface area and a porous structure on the surface.
[0041] Depend on Figure 3 It can be seen that when the simulated wood-plastic composite material is used as the substrate, the catalyst obtained in Examples 1-2 shows excellent performance in the process of catalytic pyrolysis of the simulated wood-plastic composite material. After adding the red mud-based catalyst, the yields of gaseous and liquid products increased, and the yield of solid products decreased.
[0042] Depend on Figure 4 It can be seen that when the simulated wood-plastic composite material is used as the substrate, as the pyrolysis temperature increases from 500°C to 700°C, the yield of gas phase products increases from 41.05% to 61.19%, and the yields of liquid phase products and solid phase products decrease.
[0043] Depend on Figure 5 It can be seen that when the actual wood-plastic composite material is used as the substrate, the yield of the liquid phase product increases slightly, and the yield of the solid phase product and the gas phase product decreases slightly after the red mud-based catalyst is added.
[0044] Depend on Figure 6 It can be seen that the catalyst obtained in Example 1 exhibits excellent performance in the process of catalytic pyrolysis of actual wood-plastic composite materials. It can promote the pyrolysis of actual wood-plastic composite materials to produce more aromatic oil, and the content of aromatics in the liquid product increases from 2.11% to 4.34%, thereby effectively realizing the resource utilization of waste.
[0045] The above description is only a preferred embodiment of the present invention. Any modification made to the above embodiment based on the essential technology of the present invention still falls within the protection scope of the present invention.
Claims
1. Application of a metal nickel modified red mud-based catalyst in catalytic pyrolysis of wood-plastic composite materials, the preparation method of the metal nickel modified red mud-based catalyst comprising the steps of: 1) The raw red mud is washed with deionized water, and the washed red mud is placed in a muffle furnace and calcined for 2 to 4 hours at a calcination temperature of 500 to 700°C and a heating rate of 5 to 10°C / min. The red mud is then ground and passed through a 60 to 90 mesh sieve; 2) dissolving the soluble nickel salt in deionized water, adding the red mud powder obtained above, stirring thoroughly at 50-70° C. for 5-10 hours, and drying the obtained mixed solution in a forced air drying oven at 100-120° C. to a solid product of constant weight; 3) After the solid product is cooled, it is placed in a tubular furnace, heated to 400-700°C at a heating rate of 10°C / min and reduced at a constant temperature for 5 hours to obtain a metal nickel-modified red mud-based catalyst.
2. The use according to claim 1, characterized in that The loading amount of transition metal nickel in the red mud-based catalyst is 5% to 20%.
3. The use according to claim 1, characterized in that The soluble nickel salt is nickel chloride, nickel nitrate, nickel sulfate and nickel acetate, preferably nickel nitrate.
4. The use according to claim 1, characterized in that The application method comprises the following steps: placing a transition metal nickel red mud-based catalyst and a wood-plastic composite material into a vertical tubular furnace, and performing catalytic pyrolysis in a nitrogen gas atmosphere at a pyrolysis temperature of 500-700° C. to obtain a hydrogen-rich gas phase product and an aromatics-rich liquid phase product.
5. The use according to claim 4, characterized in that The ratio of the red mud-based catalyst to the substrate in the catalytic pyrolysis process is 0% to 40%.
6. The use according to claim 4, characterized in that The nitrogen flow rate is 30 ml / min, and the pyrolysis time is 10 to 30 minutes.
7. The use according to claim 4, characterized in that The wood-plastic composite material comprises wood and plastic; the wood is wood fiber or crop straw.
8. The use according to claim 4, characterized in that The wood is pine, but is not limited to pine.
9. The use according to claim 4, characterized in that The plastic is low-density polyethylene, polyethylene, polyvinyl chloride or polypropylene, but is not limited to low-density polyethylene, polyethylene, polyvinyl chloride or polypropylene.
10. The use according to claim 9, characterized in that The mass ratio of the low-density polyethylene or polyvinyl chloride to the pine wood is 1:4.
Citation Information
Patent Citations
Preparation method of red mud supported nickel catalyst
CN104511278A
Method for preparing aromatic hydrocarbons by catalyzing pyrolysis of wood-plastic composite waste through activated carbon
CN111068727A
Green cyclic comprehensive utilization method of red mud and lignin waste
CN111073671A
Method for resourceful treatment of tobacco waste and waste plastic under catalysis of red mud
CN117801844A